Structural and chemical evolution of the CdS:O window layer during individual CdTe solar cell processing steps. (1st January 2018) - Abbas, A.; Meysing, D.M.; Reese, M.O.; Barnes, T.M.; Walls, J.M.; Wolden, C.A.
Highlights: CdS:O evolution studied as function of individual process steps. Bilayer structure formed during CdTe deposition. CdCl2 disrupts bilayer, forming CdSO4 clusters dispersed among CdS1-y Tey nanocrystals. Back contact activation does not impact front contact structure. Abstract: Oxygenated cadmium sulfide (CdS:O) is often used as the n- type window layer in high-performance CdTe heterojunction solar cells. The as-deposited layer prepared by reactive sputtering is XRD amorphous, with a bulk composition of CdS0.8 O1.2 . Recently it was shown that this layer undergoes significant transformation during device fabrication, but the roles of the individual high temperature processing steps was unclear. In this work high resolution transmission electron microscopy coupled to elemental analysis was used to understand the evolution of the heterojunction region through the individual high temperature fabrication steps of CdTe deposition, CdCl2 activation, and back contact activation. It is found that during CdTe deposition by close spaced sublimation at 600 °C the CdS:O film undergoes recrystallization, accompanied by a significant (∼30%) reduction in thickness. It is observed that oxygen segregates during this step, forming a bi-layer morphology consisting of nanocrystalline CdS adjacent to the tin oxide contact and an oxygen-rich layer adjacent to the CdTe absorber. This bilayer structure is then lost during the 400 °C CdCl2 treatment where the film transforms into a heterogeneous structure with cadmium sulfate clusters distributed randomly throughout the window layer. The thickness of window layer remains essentially unchanged after CdCl2 treatment, but a ∼25 nm graded interfacial layer between CdTe and the window region is formed. Finally, the rapid thermal processing step used to activate the back contact was found to have a negligible impact on the structure or composition of the heterojunction region.